Analisis pemahaman matematis siswa melalui discovery leraning: Sejauh mana minat belajar siswa memberi kontribusi? - Rijal, Deyjan Ahsan Nur; Ristiana, Muhammad Ghiyats; Sariningsih, Ratna; Hendriana, Heris (IKIP Siliwangi, 2025)
This research aims to determine the level of effectiveness of a model, namely discovery learning in mathematics learning, on students' mathematical understanding. This research had research subjects consisting of 18 class X SMA Budi Bakti 2 Cianjur students. Carried out using mixed methods, the instruments used were also created to measure quantitative as well as qualitative data. The data analysis used was hypothesis testing with a one-sample t test carried out on students' posttest scores. Apart from the t test, correlation and regression tests were also carried out on students' interest in learning and mathematical understanding. From the research conducted, the use of the discovery learning model is effective for application in mathematics learning in terms of mathematical understanding. The use of the discovery learning model has proven to be effective because students' mathematical understanding can exceed the KKM score. Interest in learning has a correlation with students' mathematical understanding, therefore interest in learning also has a regression towards mathematical understanding with a relatively high level of regression or a dominant influence.